Bilateral buccal exostosis evaluated by cone-beam computed tomography: A rare accidental finding - Humaira Siddiqui; Dhirendra Kumar Singh; Silpiranjan Mishra; Arnab Mandal (Wolters Kluwer Medknow Publications, 2017)
Buccal exostoses are broad-based, non-malignant surface growth occurring on the outer or facial surface of the maxilla and/or mandible, found usually in the premolar and molar region. Etiology is still not established, but it has been suggested that the bony overgrowth can be because of abnormally increased masticatory forces to the teeth. Compensatory response to periodontal disease has been proposed to explain some cases of exostoses; they tend to appear in early adolescence and may very slowly increase in size with time. They are painless, self-limiting and may increase patient concern about poor esthetics, inability to perform oral hygiene procedures, and compromised periodontal health by causing food lodgment. The following article presents a very rare case of bilateral buccal-sided maxillary and mandibular exostoses in the anterior region which was an accidental finding in a chronic generalized periodontitis patient.